(untitled) (Interdisciplinary Research in Education, 2024)
This article explores teachers’ perceptions of integrating ChatGPT in Nepalese classrooms. Using a qualitative research design, the study examines the viewpoints and experiences of teacher participants to gain an understanding of context, meanings, and subjective perspectives using ChatGPT. In-depth interviews were conducted with five teacher educators and five school teachers, capturing insights from both university and school classroom environments. Purposive sampling ensured the deliberate selection of participants from the Faculty of Education, Tribhuvan University and schools in the Kirtipur municipality. The data analysis involves transcription, translation, coding, decoding, and the creation of themes, sub-themes, and categories, enabling an exploration of the study’s issues. The study found that teachers perceive ChatGPT as a useful tool for deepening classroom instruction, particularly in providing personalized learning experiences. However, concerns were raised regarding the potential over-reliance on the technology, emphasizing the need for proper training and guidelines to ensure its effective integration in Nepalese educational settings. This study contributes valuable insights for educators and teachers interested in integrating ChatGPT into educational settings, with the ultimate goal of informing the development of strategies for the effective use of this technology in Nepalese classrooms.